Perencanaan Desain Gambar Pembangunan Meunasah Al-Istiqamah Suak Ribee Sebagai Upaya Menciptakan Tempat Ibadah yang Berseri - Mahmudin Marbun; Teuku Farizal; Syurkarni Ali; Zulyaden Zulyaden (Universitas Teuku Umar, 2021)
Building design is one of the right ways of the building which get the hope of the comfortable building, radiant building and it’ ll have get peaced on it, The right step begins in the design. of the building. Meunasah Al – Istiqamah, is a place of worship for the people’s residents of Dusun 3 Suak Ribee. Which Earthquake-prone areas, in the implementation of development are highly recommended to refer to building standardization, especially SNI. 1726-2013 and The reinforced concrete standardization refers to SNI 2847:2013. The method of implementing community service activities (PKM) is carried out for 3 (three) months. This PkM wants to be fostered in the process of building Meunasah Al Istiqamah accordance with of the community hopeness and the outcomes of building construction according to the required standards. Provide understanding to the community and workers with work methods in accordance with technical specifications for buildings, referring to existing standards, assisting communities in accommodating the amount of development costs in accordance with the specified design. The desired output for the surrounding community is the occurrence of a community culture to build according to technical specifications, planning the construction of public facilities exactly according to the plan. The results obtained are that the design has been carried out by producing both 2D and 3D design drawings with the concept of the comfortable buildings